2023
DOI: 10.1097/j.jcrs.0000000000001140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of implantable collamer lens sizing developed by reviewing the horizontal compression-vault coefficient

Abstract: To evaluate the implantable collamer lens (ICL)-sizing method using the partial regression coefficient of the implanted ICL size to review the conventional horizontal compression coefficient and match the results of clinical observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
(42 reference statements)
0
17
0
2
Order By: Relevance
“…Notably, none of the nomograms compared in this study used ACA as a parameter for predicting vault. [8][9][10][12][13][14][15][16][17]29 When evaluating the utility of various nomograms, one must also consider the ease of use for required preoperative measurements which may not be available in all practice settings. Although clinicians have historically used STAAR and Optimized WTW, followed by the implementation of UBM, which allowed for the use of Parkhurst and Dougherty, the authors found Kim, Rocamora, Reinstein, and Russo to be the highest performing for the prediction of postoperative vault.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, none of the nomograms compared in this study used ACA as a parameter for predicting vault. [8][9][10][12][13][14][15][16][17]29 When evaluating the utility of various nomograms, one must also consider the ease of use for required preoperative measurements which may not be available in all practice settings. Although clinicians have historically used STAAR and Optimized WTW, followed by the implementation of UBM, which allowed for the use of Parkhurst and Dougherty, the authors found Kim, Rocamora, Reinstein, and Russo to be the highest performing for the prediction of postoperative vault.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, none of the nomograms compared in this study used ACA as a parameter for predicting vault. 8–10,12–17,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinstein et al developed a formula which uses the inner diameter of the ciliary body, scotopic pupil diameter, and other parameters to predict vault size with an accuracy of ± 300 µm in 94-100 % of eyes [78]. Using several parameters based on anterior segment optical coherence tomography, Nakamura et al were able to achieve a vault size of between 250 and 1,000 µm in 90.6 % of eyes [80].…”
Section: Postoperative Factors Influencing Endothelial Cell Lossmentioning
confidence: 99%
“…Um die Vorhersagbarkeit zu erhöhen, wurden alternative Berechnungsmethoden vorgeschlagen. Die neuesten Studien konnten eine bessere Vorhersagbarkeit des Vaults erreichen, indem sie mehrere auf optischer Kohärenztomografie des Vorderabschnittes und auf Ultraschall-Biomikroskopie basierte Parameter verwendeten 78 , 79 , 80 . Reinstein et al entwickelten eine Formel, die anhand des Innendurchmessers des Ziliarkörpers, des Pupillendurchmessers bei skotopischen Lichtbedingungen und anderer Parameter den Vault mit einer Genauigkeit von ± 300 µm bei 94 – 100% der Augen vorhersagen konnte 78 .…”
Section: Postoperative Faktoren Die Den Endothelzellverlust Beeinflussenunclassified